2018
DOI: 10.1038/s41401-018-0078-7
|View full text |Cite
|
Sign up to set email alerts
|

CZ-7, a new derivative of Claulansine F, ameliorates 2VO-induced vascular dementia in rats through a Nrf2-mediated antioxidant responses

Abstract: Vascular dementia (VD) results from accumulated damage in the vascular system, which is characterized by progressive impairments in memory and cognition and is second only to Alzheimer's disease (AD) in prevalence among all types of dementia. In contrast to AD, there is no FDA-approved treatment for VD owing to its multiple etiologies. In this study, we investigated whether CZ-7, a new derivative of Claulansine F (Clau F) with verified neuroprotective activity in vitro, could ameliorate the cognitive impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…Bilateral common carotid artery occlusion (BCCAO) was established to study the cognitive dysfunction and neurodegeneration caused by chronic cerebral hypoperfusion (CCH). The BCCAO surgery was performed as previously conducted in our laboratory [ 1 ]. Thirty-two Sprague-Dawley rats were randomly divided into 2 groups, namely, the sham group ( n = 8) and the BCCAO group ( n = 24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilateral common carotid artery occlusion (BCCAO) was established to study the cognitive dysfunction and neurodegeneration caused by chronic cerebral hypoperfusion (CCH). The BCCAO surgery was performed as previously conducted in our laboratory [ 1 ]. Thirty-two Sprague-Dawley rats were randomly divided into 2 groups, namely, the sham group ( n = 8) and the BCCAO group ( n = 24).…”
Section: Methodsmentioning
confidence: 99%
“…Vascular dementia (VD) is the second most common dementia-related disease in the world after Alzheimer’s disease (AD) [ 1 , 2 ]. The risks of VD increase with age, and the severity of VD depends on injury to vessels and cerebral regions.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanism of oxidative stress-induced cognitive deficits has been investigated in animal models. In occlusion rat models (BCAO), it was shown that oxidative stress is characterized by the increased production of reactive oxygen species (ROS) [58,59] which are responsible for both cardiovascular pathophysiology and neurodegeneration [60,61]. In fact, ROS and reduced antioxidant defense may directly affect synaptic activity and neurotransmission in neurons, leading to cognitive dysfunction [62].…”
Section: Molecular Mechanism Of Vcimentioning
confidence: 99%
“…In fact, ROS and reduced antioxidant defense may directly affect synaptic activity and neurotransmission in neurons, leading to cognitive dysfunction [62]. In the same models, it was also shown that the negative effects of ROS on memory processes could be counteracted by substances able to increase the gene expression of antioxidant proteins, such as nuclear factor erythroid 2 like 2 (NFE2L2), alcohol dehydrogenase 7 (ADH7), and glutathione peroxidase 2 (GPX2) and 3 (GPX3) [58,59].…”
Section: Molecular Mechanism Of Vcimentioning
confidence: 99%
“…More importantly, CZ-7 exposure in the brain was 4.3-fold higher than that in plasma, and preliminary acute toxicological test results showed that CZ-7 had no toxic side effects with an oral 1 g/kg dose in ICR (Institute of Cancer Research) mice [ 16 ]. In addition, CZ-7 has therapeutic potential for VD (vascular dementia) by alleviating oxidative stress injury through Nrf2-mediated antioxidant responses [ 17 ].…”
Section: Introductionmentioning
confidence: 99%